The Impact of E-Service Quality Towards Customer Loyalty Mediated by Customer Perceived Value in the Case of Go-Jek - Kevin Chandra Santoso; Kenanya Rubino (iBuss Management, 2021)
This research aims to examine the effect of e-service quality on customer perceived value and customer loyalty. Currently, e-service quality is very crucial for an online service provider company such as Go-Jek. Go-Jek as a brand is the subject of this research due to their high capability in providing daily service necessities. Moreover, this research model will be developed from the existing research model by Jiang et al. (2016) which includes the key dimension of e-service quality which are care, reliability, security, ease of use, and product portfolio. Based on a survey of 100 respondents using multiple regression analysis method, the researchers identified that e-service quality shows significant and positive impacts on customer perceived value and customer loyalty. The researchers further found that customer perceived value as the mediating variable has a negative relationship with customer loyalty. The results suggest there is an occurrence of a partial mediation role in the effect of e-service quality towards customer loyalty. Companies such as Go-Jek would benefit from the results that is presented in this research in an effort to improve their service performance to further retain customers.Keywords:E-service Quality, Customer Perceived Value, Customer Loyalty.